2021
DOI: 10.1371/journal.pone.0250735
|View full text |Cite
|
Sign up to set email alerts
|

Race and ethnicity do not impact eligibility for remdesivir: A single-center experience

Abstract: As the Coronavirus-2019 (COVID-19) pandemic continues, multiple therapies are rapidly being evaluated for efficacy in clinical trials. Clinical trials should be racially and ethnically representative of the population that will eventually benefit from these medications. There are multiple potential barriers to racial and ethnic minority enrollment in clinical trials, one of which could be that inclusion and exclusion criteria select for certain racial or ethnic groups disproportionately. In this observational … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…It is important to address historical, ethical, environmental, and cultural biases at the institutional, community, and patient levels to increase diversity in clinical trial enrollment. 7,10,13,20,33 There is considerable variability in the trial participation of certain ethnic or racial populations even when trials are conducted by the same sponsor. For example, in an analysis of Pfizer trials, Rottas et al 16 found that Black patient participation was variable across different therapeutic areas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is important to address historical, ethical, environmental, and cultural biases at the institutional, community, and patient levels to increase diversity in clinical trial enrollment. 7,10,13,20,33 There is considerable variability in the trial participation of certain ethnic or racial populations even when trials are conducted by the same sponsor. For example, in an analysis of Pfizer trials, Rottas et al 16 found that Black patient participation was variable across different therapeutic areas.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies to substantiate conclusions made by authors of the selected articles are needed for identifying the context in which low enrollment occurred (eg, lack of eligibility or inadequate enrollment techniques for underrepresented groups). 33 For example, only 1 study in our review mentioned racial and ethnic differences between Phase 1 and Phase 3 trials. 27 Differences between Phase 1 and Phase 3 trial participation (eg, age, race, ethnicity, household income) may be related to variations in recruitment practices (eg, location of clinics, physician involvement, financial compensation).…”
Section: Methods For Defining Diversitymentioning
confidence: 99%
See 3 more Smart Citations